Efektivitas Klinis Akupunktur dalam Mengurangi Nyeri Kepala Sindrom Liver Fire: Studi Kasus - Dewi Jeni; Amal Prihatono; Chantika Mahadini (JURNAL BIDANG ILMU KESEHATAN, 2026)
Cephalgia, encompassing migraine and tension-type headache (TTH), is a major global health burden characterized by high disability rates. The limitations of conventional pharmacotherapy, including the risk of medication-overuse headache (MOH) and potential organ toxicity, highlight the urgent need for safer and more sustainable complementary approaches. Traditional Chinese Medicine (TCM) offers a holistic solution through the concept of Bian Zheng Lun Zhi (syndrome differentiation), particularly for Liver Fire syndrome frequently associated with high-intensity chronic headaches. This research is a clinical case study on one 42-year-old female patient diagnosed with migraine without aura and TTH exhibiting Liver Fire manifestations, aiming to evaluate the clinical efficacy of a standardized six-point acupuncture protocol (LR3, GB20, LI4, EX-HN5, GB34, and SP6). The intervention consisted of twelve sessions over six weeks. Results demonstrated significant clinical improvement, with Visual Analog Scale (VAS) scores decreasing from 8 to 0 and the absence of pain attacks at the end of the therapy period. Furthermore, objective TCM parameters indicated a restoration of physiological balance. These findings confirm that acupuncture effectively alleviates cephalgia by targeting the underlying pathology of Liver Fire syndrome through therapeutic mechanisms involving the down-regulation of neurogenic inflammation (CGRP, SP), restoration of mitochondrial function, and modulation of the autonomic nervous system